Media Game Edukasi Berbasis Konservasi pada Tema Lingkungan di TK PKK Sikur Barat 01 - Lia Rismawati (Lembaga Bale Literasi, 2022)
This study aims to produce valid and effective learning media. This type of research is research and development (R & D) using the Borg and Gall model modified by Sukmadinata covering three stages, namely: (1) preliminary study; (2) preparation of product drafts; and (3) development. The learning media developed is the